Heterogeneity in the guidelines for the management of diabetic foot disease in the Caribbean - Bauer E. Sumpio; Simone McConnie; Dale Maharaj (Public Library of Science (PLoS), 2022)
The prevalence of diabetes mellitus, diabetic foot (DF) disease and, as a result, lower extremity amputation rates remain high in the Caribbean. This study was undertaken to determine whether Caribbean countries have designated individuals that monitor DF disease and whether there are DF protocols consistent with the International Working Group on the Diabetic Foot (IWGDF) guidance documents. Relevant DF health care personnel(s) from the CARICOM and Dutch Caribbean countries were called or sent questionnaires regarding the presence of structured programs to monitor and manage DF problems in the population. All 25 countries (100%) responded. 81% of respondents could not identify any Ministry, Hospital or individual initiatives that monitored the DF. Only 9 (36%) countries had any guidelines in place. Only 3 countries with guidelines in place utilized IWGDF guidelines. Only 6 (24%) countries had podiatrists and 10 (40%) had vascular surgery availability. 7 (28%) countries had the components for a multidisciplinary team. The presence or the appointment of a designated individual and/or a multidisciplinary approach within the countries for DF disease was absent in the majority of respondent countries. Only a minority of countries implemented DF guidelines or had expertise available to organize a DF multidisciplinary team. Vascular surgery and podiatric care were noticeably deficient. These may be critical factors in the variability and reduced success in implementation of strategies for managing DF problems and subsequent amputations amongst these Caribbean countries.